Serum Level of CCL20 and CXCL 10 in Patients with Vitiligo and their Association with Disease Activity - Zainab R. AL-Mousawi; Alaa S. Alattabi; Dhamiaa M. Hamza; Fatima A. AL-Hussiny (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aim of Study: study the level of CCL20 and CXCL 10 in serum of patients with vitiligo ,to compare theirlevel in patients with active vitiligo and stable vitiligo and compare level of each cytokine with others Toknow their association with disease activity.Materials/Methods: Sixty-five patients who include (35 active and 30 stable) with vitiligo. All participantsincluded were adult patients with nonsegmental vitiligo.Blood sample were collected by venipuncture from 65 patients (five millimeter of venous were drawing bydisposable syringe under sterilization technique and putting in gel tube then, allowed to clot; after that serumwas separated by centrifugation 1500 rpm for 5 minute. The serum has been collected in plain tube thenstored at -20c to be used for ELISA test to determine concentration of CCL20 and CXCL 10. The resultswere analyzed using the IBM SPSS analytic software.Result: The : current study revealed thatCCL20 are significant (P<0.05), while CXCL10 was not significant(P>0.05) according to the disease activity. The sensitivity and specificity of each of the measured biomarkerswas evaluated using the (ROC). It was found that CCL20 to be of a high significance to measuring thedisease activity. While the CXCL10 was of no significance when compared to the disease activityConclusions: CCL20 could be candidate as a biomarker to evaluate activity of vitiligo